An existence result for anisotropic quasilinear problems. (June 2022) - Agudelo, Oscar; Drábek, Pavel
Abstract: We study existence of solutions for a boundary degenerate (or singular) quasilinear equation in a smooth bounded domain under Dirichlet boundary conditions. We consider a weighted p -Laplacian operator with a coefficient that is locally bounded inside the domain and satisfying certain additional integrability assumptions. Our main result applies for boundary value problems involving continuous non-linearities having no growth restriction, but provided the existence of a sub and a supersolution is guaranteed. As an application, we present an existence result for a boundary value problem with a non-linearity f ( u ) satisfying f ( 0 ) ≤ 0 and having ( p − 1 ) -sublinear growth at infinity.